2010
DOI: 10.1590/s0100-204x2010001100009
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis que influenciam a produção de celulases e xilanase por espécies de Aspergillus

Abstract: Resumo -O objetivo deste trabalho foi determinar as variáveis que influenciam a produção simultânea de celulases e xilanase por Aspergillus aculeatus URM 4953 e A. phoenicis URM 4924, com uso de bagaço de cana-de-açúcar como substrato. As variáveis avaliadas foram pH inicial, tempo de cultivo, concentração do substrato, agitação, concentração do inóculo, temperatura, tipo de bagaço de cana-de-açúcar e espécie de Aspergillus. Foi utilizado o planejamento fatorial fracionário 2 , com três repetições no ponto ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
7
0
5
Order By: Relevance
“…The greatest biosynthesis of xylanase at 45 o C suggests that A. fumigatus SCB4 can be a thermotolerant fungal strain. Previous studies reported the effects of time and temperature during SSF on xylanase synthesis by other Aspergillus species and described higher production of xylanases at the same temperature (SALES et al, 2010, DELABONA et al, 2012. This peak of xylanase activity at 45 o C suggest that this mold can be employed in bioreactors at high temperatures, which could contribute to better conditions of operations, such as fluidity of the medium and reduction of the risk of contamination by mesophilic microorganisms (GOMES et al, 2007).…”
Section: Resultsmentioning
confidence: 82%
“…The greatest biosynthesis of xylanase at 45 o C suggests that A. fumigatus SCB4 can be a thermotolerant fungal strain. Previous studies reported the effects of time and temperature during SSF on xylanase synthesis by other Aspergillus species and described higher production of xylanases at the same temperature (SALES et al, 2010, DELABONA et al, 2012. This peak of xylanase activity at 45 o C suggest that this mold can be employed in bioreactors at high temperatures, which could contribute to better conditions of operations, such as fluidity of the medium and reduction of the risk of contamination by mesophilic microorganisms (GOMES et al, 2007).…”
Section: Resultsmentioning
confidence: 82%
“…niger, A. awamori, A. oryzae, A. nidulans, A. fumigatus, A. clavatus, A. glaucus, A. ustus, and A. versicolor (SLIVINSKI, 2007). Also in this genus, the species from the Nigri section have been extensively studied, as they are good producers of enzymes such as amylase, cellulose, pectinase, protease, and phytase (SALES et al, 2010;RODRÍGUEZ et al, 2011;REZENDE et al, 2012;MACIEL, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulases are enzymes that form a complex that hydrolyses cellulosic materials, releasing sugars [2]. The main component of hemicellulose is the xylan, which is hydrolyzed by xylanases [3]. Cellulases as xylanases have a great biotechnological potential, they can be used in a variety of field: food, animal feed, textile and paper recycling industries.…”
Section: Introductionmentioning
confidence: 99%